A new approach to access difluoroalkylated diarylmethanes via visible-light photocatalytic cross-coupling reactions. Issue 32 (3rd April 2018) - Zhao, Yin-Na; Luo, Yong-Chun; Wang, Zhu-Yin; Xu, Peng-Fei
Abstract : A para -quinone methide and difluoroalkylating reagent involved radical cross-coupling reaction was described, through photocatalytically generated diarylmethane radical intermediates. Abstract : Difluoroalkylated diarylmethanes with biological and pharmacological potentials were synthesized from para -quinone methides ( p -QMs) and difluoroalkylating reagents via a visible light photocatalysis strategy. Mechanism studies showed that the excited photocatalyst, * fac -Ir(ppy)3, was primarily quenched by p -QMs and the generated diarylmethane radical intermediates then underwent a radical–radical cross-coupling reaction with difluoroalkyl radicals. This reaction features mild conditions, high efficiency and wide functional group compatibility.